2013
DOI: 10.4037/ajcc2013700
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Critical-Care Pain Observation Tool in Intubated Adults After Cardiac Surgery

Abstract: Background Pain assessment in critically ill patients who are intubated, sedated, and unable to verbalize their needs remains a challenge. No universally accepted pain assessment tool is used in all intensive care units. Objectives To examine concurrent validation of scores on the Critical-Care Pain Observation Tool for a painful and a nonpainful procedure and to examine interrater reliability of the scores between 2 nurse raters. Methods A prospective, repeated-measures within-subject design was used. A conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
1
17
0
8
Order By: Relevance
“…79 A recent validation study 80 in a sample of 30 intubated cardiac surgery patients supports the previous research findings that the CPOT has acceptable interreliability and concurrent validity.…”
Section: Pain Assessment and Controlsupporting
confidence: 53%
“…79 A recent validation study 80 in a sample of 30 intubated cardiac surgery patients supports the previous research findings that the CPOT has acceptable interreliability and concurrent validity.…”
Section: Pain Assessment and Controlsupporting
confidence: 53%
“…Use of the CPOT has had positive effects on nurses’ pain assessment and documentation, and may affect treatment processes, mechanical ventilation time and ICU length of stay 41 , but its effects on patients’ pain outcomes remain to be evaluated. The CPOT’s reliability and validity have been confirmed in several small studies conducted by other investigators 42,43 , although one 42 noted lower inter-rater reliability than initial studies and suggested the use of standardized instructions and training. Others have extended the use of the CPOT to neurological intensive care unit patients who had brain surgery 44 and critically ill patients with delirium 45 , but unfortunately both French and English versions were used and treated as one in the analysis.…”
Section: Review Of Selected Pain Assessment Toolsmentioning
confidence: 81%
“…This is consistent with other findings (Gardner et al , ). When patients go through endotracheal intubation, pain management seems extremely important and a reliable observation tool and adequate pain management are crucial (Linde et al , ; Stites, ).…”
Section: Discussionmentioning
confidence: 99%